Classroom Ethnographic Study: Teacher and Student Interaction in Sociology Learning in Class XI IPS MAN 1 Medan - Dwi Zahara Silvia; Muhammad Iqbal (CV. Rayyan Dwi Bharata, 2024)
This research aims to analyze teacher and student interactions in sociology learning and identify obstacles in teacher and student interactions in sociology learning in class XI IPS MAN 1 Medan. The method used in this research is qualitative research with an ethnographic approach. Research data collection techniques through participant observation, in-depth interviews, documentation and field notes. The research results show that good interactions between teachers and students contribute positively to student relationships and engagement. Teachers succeed in building effective relationships through emotional connection, positive communication, forming good habits, and support through good feedback. In the sociology learning process, starting from the opening activity, core activity and closing activity, teacher and student interactions form certain patterns, namely one-way interaction which occurs if only the teacher gives action to students, then its nature then changes to two-way when there is a reaction by the participants. students, and becomes multidirectional when interactions are more complex, for example during presentation activities. This research also found that there were obstacles in the interaction between teachers and students. Such as lack of response and participation and time constraints make it difficult for teachers to understand their specific needs. And the obstacles for students are mainly psychological and emotional obstacles such as lack of self-confidence and shyness to be active and participate in class.